The representation of public values in health technology assessment to inform funding decisions: the case of Australia's national funding bodies. (18th January 2021) - Haji Ali Afzali, Hossein; Street, Jackie; Merlin, Tracy; Karnon, Jonathan
Abstract: Over the past few years, there has been an increasing recognition of the value of public involvement in health technology assessment (HTA) to ensure the legitimacy and fairness of public funding decisions [Street J, Stafinski T, Lopes E, Menon D. Defining the role of the public in Health Technology Assessment (HTA) and HTA-informed decision-making processes. Int J Technol Assess Health Care . 2020;36:87–95]. However, important challenges remain, in particular, how to reorient HTA to reflect public priorities. In a recent international survey of thirty HTA agencies conducted by the International Network of Agencies for HTA (INAHTA), public engagement in HTA was listed as one of the "Top 10" challenges for HTA agencies [O'Rourke B, Werko SS, Merlin T, Huang LY, Schuller T. The "Top 10" challenges for health technology assessment: INAHTA viewpoint. Int J Technol Assess . 2020;36:1–4]. Historically, Australia has been at the forefront of the application of HTA for assessing the effectiveness and cost-effectiveness of new health technologies to inform public funding decisions. However, current HTA processes in Australia lack meaningful public inputs. Using Australia as an example, we describe this important limitation and discuss the potential impact of this gap on the health system and future directions.